Clinical variables associated with functional deficits in patients affected by chronic chikungunya arthralgia: A cross-sectional study - Sacha Cunha Brito Holanda, Joanna; Fonseca Mendes, Eduarda; Silva-Filho, Edson; Cecilia Queiroz de Medeiros, Anna; Di-Bonaventura, Silvia; Pegado, Rodrigo (Journal of back and musculoskeletal rehabilitation, 2025)
BackgroundChikungunya virus is an endemic arbovirus that affects populations worldwide. Its primary debilitating symptoms include inflammatory arthralgia, functional incapacity, and pain.ObjectiveThis study aims to identify factors predicting altered functional capacity in patients affected by chronic chikungunya arthralgia.MethodsThis is a cross-sectional study conducted from October 2023 to June 2024. Data were collected using the following instruments: the Health Assessment Questionnaire, the Visual Analogue Scale, the Brief Pain Inventory, the Pittsburgh Sleep Quality Index, and the Short Form-36 Health Survey. Regression analysis was performed to identify associations among the variables.ResultsWe included 119 individuals infected by the Chikungunya virus. Regression analysis of VAS scores revealed that age (coefficient: -0.5532, = 0.016) and BPI Intensity (coefficient: 1.1716, = 0.002) were significant predictors. Older age was associated with lower VAS scores, while higher BPI Intensity correlated with higher VAS scores. The model explained 25.7% of VAS score variability (R-squared: 0.257). For HAQ scores, age (coefficient: -0.0104, = 0.039), PSQI (coefficient: 0.2250, = 0.002), and SF36 Physical Health (coefficient: -0.0118, = 0.005) were significant predictors, accounting for 31.6% of the variability (R-squared: 0.316).ConclusionThere is significant complexity in the signs and symptoms exhibited by individuals infected with the chikungunya virus. We highlight the identification of significant associations between pain and disability in individuals affected by the Chikungunya virus.